Efficacy of anlotinib and chemotherapy combination as neoadjuvant therapy in the treatment of pulmonary artery intimal sarcoma: a case report - Liang, Gai; Zhang, Qu; Luo, Yan; Zhao, Yuanhua; Luo, Bo (Frontiers in Oncology, 2025)
Pulmonary arterial intimal sarcoma (PAIS) is a rare malignant mesenchymal tumor often associated with an unfavorable prognosis and lacks a standardized treatment approach to date. This report presents a notable case of PAIS treated with neoadjuvant therapy involving anlotinib concomitantly administered with chemotherapy of ifosfamide and pirarubicin, which resulted in a favorable outcome. A 38-year-old man was admitted to our hospital with chest tightness, cough, and dyspnea, all of which had persisted for more than a week. Initial evaluation via chest computed tomography (CT) revealed a sizable posterior mediastinal tumor measuring 11.9 × 7.6 cm. A CT-guided biopsy was performed, and pathological findings confirmed the diagnosis of PAIS. Efficacy evaluation showed slow progress after one cycle of chemotherapy with ifosfamide and pirarubicin. To enhance treatment outcomes, we incorporated anlotinib as a neoadjuvant therapy alongside ifosfamide and pirarubicin. Subsequent CT imaging demonstrated a significant reduction in tumor size, and the patient experienced notable alleviation of symptoms. The patient then underwent surgery, radiation, and subsequently, maintenance treatment with anlotinib for one year. No severe drug-related side effects were observed. The patient achieved progression-free survival of 25 months following administration of anlotinib. Thus, the combination of anlotinib with ifosfamide and pirarubicin demonstrated significant efficacy and safety. This approach holds promise as an effective therapeutic strategy for managing unresectable, locally advanced, or advanced PAIS. However, further clinical studies are necessary to validate these findings.